Combined Pharmacological Inhibition of Cyclophilins, FK506-Binding Proteins, Hsp90, and Hsp70 Protects Cells From Clostridium botulinum C2 Toxin - Ernst, Katharina; Kling, Carolin; Landenberger, Marc; Barth, Holger (Frontiers in Pharmacology, 2018)
The Clostridium botulinum C2 toxin is an exotoxin causing severe enterotoxic symptoms. The C2 toxin consists of the binding/translocation component C2II and the enzymatic active component C2I. After proteolytic activation, C2IIa forms heptamers that bind C2I. The C2IIa/C2I complex is taken up into mammalian target cells via receptor-mediated endocytosis. Acidification of endosomes leads to conformational changes in both components. C2IIa heptamers from a pore into the endosomal membrane and C2I becomes unfolded and translocates through the narrow C2IIa pores into the cytosol of the cell. Here, C2I covalently transfers an ADP-ribose moiety from its co-substrate NAD+ onto G-actin which leads to depolymerization of F-actin resulting in rounding up of adherent cells. Translocation of C2I into the cytosol depends on the activity of the chaperones Hsp90 and Hsp70 and peptidyl-prolyl cis/trans isomerases of the cyclophilin (Cyp) and FK506-binding protein (FKBP) families. Here, we demonstrated that C2I is detected in close proximity with Hsp90, Cyp40 and FKBP51 in cells, indicating their interaction. This interaction was dependent on the concentration of C2 toxin and detected in mammalian Vero and human HeLa cells. Moreover, the present study reveals that combination of radicicol, VER-155008, cyclosporine A and FK506, which are specific pharmacological inhibitors of Hsp90, Hsp70, Cyps and FKBPs respectively, resulted in a stronger inhibition of intoxication of cells with C2 toxin compared to application of the single inhibitors. Thus, the combination of inhibitors showed enhanced protection of cells against the cytotoxic effects of C2 toxin. Cell viability was not significantly impaired by application of the inhibitor combination. Moreover, we confirmed that the combination of radicicol, VER-155008, CsA and FK506 in particular inhibit the membrane translocation step of C2I into the cytosol whereas receptor binding and enzyme activity of the toxin were not affected. Our findings further characterize the mode of action of Hsp90, Hsp70, Cyps and FKBPs during membrane translocation of bacterial toxins and furthermore supply starting points for developing of novel therapeutic strategies against diseases caused by bacterial toxins that depend on Hsp90, Hsp70, Cyps and FKBPs.